The Pagodroma Group - a Cenozoic record of the East Antarctic ice sheet in the northern Prince Charles Mountains - McKelvey, BC; Hambrey, MJ; Harwood, DM; Mabin, MCG; Webb, PN; Whitehead, JM (2001)
The northern Prince Charles Mountains overlook the western side of the 700 km long Lambert Glacier-Amery Ice Shelf drainage system. Within these mountains, at Amery Oasis (70°50'S, 68°00'E) and Fisher Massif (71°31'S, 67°40'E), the Cenozoic glaciomarine Pagodroma Group consists of four uplifted Miocene and Pliocene-early Pleistocene formations here named the Mount Johnston, Fisher Bench, Battye Glacier and Bardin Bluffs formations. These are composed of massive and stratified diamicts, boulder gravels and minor laminated sandstones, siltstones and mudstones. Each formation rests on either Precambrian metamorphic rocks, or on Permo-Triassic fluvial strata. The unconformity surfaces are parts of the walls and floors of palaeofjords. The Miocene Fisher Bench Formation exceeds 350 min thickness at Fisher Massif, where the yet older Miocene (or Oligocene) Mount Johnston Formation overlies basement rocks at up to 1400 m above sea level. Individual formations contain either Miocene diatoms, or else Pliocene-early Pleistocene diatomforam assemblages. The diamicts are interpreted as fjordal ice-proximal or ice-contact sediments, deposited seawards of tidewater glacier fronts located some 250 to 300 km inland of the present ocean margin. Each formation records an ice recession following a glacial expansion.